Effects Of Video-Podcasts On Listening Comprehension Of Saudi EFL Learners - Shahid, Shahid Hussain; Zuraina, Ali (Open Access Publishing Group, 2017)
The current use of podcasts, as a new channel to input knowledge, has effectively been promoting listening comprehension which consequently has increased the acquisition of target language. The objective of the present study is to investigate the effects of video-podcasts integration on listening comprehension. The twelve-week quantitative study employed a quasi-experimental pre-test post-test design. Samples included in both the control and experimental groups were 120 English major male undergraduates from a University in Saudi Arabia. The Findings of ANCOVA analysis showed that the video-podcast group significantly outperformed the control group on the post-test. The findings imply that video-podcasts are useful resource for enhancing EFL learners’ listening comprehension.